MOBILE DEVICE FOR ASSESSING THE QUALITY OF MASKERS NOISE INTERFERENCE - Seilova Н.; Batyrgaliyev, A.; Jangozin Ж.; Gorlov Л.; Nurgabilov Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The protection of information of limited access from leakage through the channel of spurious electromagnetic radiation is solved by organizational or technical measures using passive or active means of protection. Passive protection methods include shielding, grounding, decoupling and filtering, and active methods include the use of systems of spatial electromagnetic noise and imitating (masking) interference. The use of passive methods for protecting computer equipment is the most preferable, since when using them, there are no problems associated with electromagnetic compatibility and the presence of unmasking signs of the operation of protective equipment. However, the use of passive methods for protecting computer equipment is not always possible due to the complexity of their implementation, high cost, the need for additional development work, etc. In such cases, active protection methods are used that create an increased background of the electromagnetic field, thereby masking the informative signal. The paper considers a means for measuring masking noise interference of active protection equipment based on SDR receivers. This device is applicable in determining the quality of noise interference as part of the evaluation of the effectiveness of noise generators.